Is a high‐altitude meteorological analysis necessary to simulate thermosphere‐stratosphere coupling?. Issue 19 (8th October 2015) - Siskind, D. E.; Sassi, F.; Randall, C. E.; Harvey, V. L.; Hervig, M. E.; Bailey, S. M.
Abstract We compare simulations of mesospheric tracer descent in the winter and spring of 2009 with two versions of the Whole Atmosphere Community Climate Model (WACCM), both with specified dynamics. One is constrained with data from the Modern‐Era Retrospective Analysis for Research and Applications which extends from 0 to 50 km; the other uses the Navy Operational Global Atmospheric Prediction System‐Advanced Level Physics High Altitude (NOGAPS‐ALPHA) which extends up to 92 km. By comparison with Solar Occultation for Ice Experiment data we show that constraining WACCM to NOGAPS‐ALPHA yields a dramatic improvement in the simulated descent of enhanced nitric oxide (NO) and very low methane (CH4). We suggest that constraining to NOGAPS‐ALPHA compensates for an underestimate of nonorographic gravity wave drag in WACCM. Other possibilities, such as missing energetic particle precipitation or underestimated eddy diffusion, are less likely for the Arctic winter and spring of 2009.